Compounded normal modes of free vibration of cantilever plates - Kirk, Colin L. (College of Aeronautics, 1967)
Experimental determination of the natural frequencies of a stiffened cantilever plate reveals the simultaneous excitation of two normal modes of vibration. Comparison is made between the experimental nodal pattern and the nodal pattern calculated by assuming characteristic beam functions for the vibration form of the plate.